2012
DOI: 10.3892/or.2012.1719
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-155 is downregulated in gastric cancer cells and involved in cell metastasis

Abstract: Abstract. , an important multifunctional microRNA, has been implicated in the development of multiple solid tumors, yet, its role in gastric cancer cells has not been fully elucidated. In this study, we find that miR-155 was significantly downregulated in gastric cancer cell lines compared with an immortalized gastric epithelial cell line (GES-1). Overexpression of miR-155 in SGC-7901 and MKN-45 gastric cancer cells dramatically suppressed cell migration, invasion and adhesion in vitro. Overexpression of miR-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 29 publications
5
48
0
2
Order By: Relevance
“…The presented results suggested that CCAT1 overexpression was likely to affect the downstream target miRNA level in oral tumors via sponging mechanism as shown in other cancers (9,14). In addition, CCAT1 overexpressed samples expressed a low level of miR155 and let7b and the same has been frequently reported to be deregulated in several cancer cell lines and cancers (31). All these observations suggest that CCAT1 overexpression may serve an important role in oral carcinogenesis and treatment response.…”
Section: Ccat1 Expression Level -------------------------------------supporting
confidence: 62%
“…The presented results suggested that CCAT1 overexpression was likely to affect the downstream target miRNA level in oral tumors via sponging mechanism as shown in other cancers (9,14). In addition, CCAT1 overexpressed samples expressed a low level of miR155 and let7b and the same has been frequently reported to be deregulated in several cancer cell lines and cancers (31). All these observations suggest that CCAT1 overexpression may serve an important role in oral carcinogenesis and treatment response.…”
Section: Ccat1 Expression Level -------------------------------------supporting
confidence: 62%
“…It has been confirmed that the development and progression of gastric cancer may be attributed to miRNAs [4][5][6][7][8]. In our previous work, by comparing the miRNA expression profile in 28 gastric cancer tissues and their adjacent non-tumor tissues, we found numerous putative miRNAs of differential expression [9,10]. Of them in addition to the well-known miRNAs, such as miR-375, miR-29c, miR-31, miR-199-3p, miR-409-3p [11] and miR-200 family, we noticed that miR-625 was rarely researched and was one of the most significantly down-regulated miRNAs in gastric cancer.…”
Section: Introductionmentioning
confidence: 61%
“…miR-137 is related to CDC42 inactivation and inhibition of cell growth and induction of apoptosis in gastric cancer cells [29]. In gastric cancers, miR-155 is methylated and down-regulated and conversely, overexpression of miR-155 can inhibit cell migration, invasion, and adhesion by targeting 3' UTR of SMAD2 in TGF-β pathway [30].CDK4, CCNF2, and CCNA2 are cell cycle-related genes that are targeted by miR34b and miR-34c, which are also silenced epigenetically by methylation in gastric cancers [31]. miR-129 is methylated and down-regulated in primary gastric tumors, leading to SOX4 gene being upregulated in gastric cancers.…”
mentioning
confidence: 99%